Baricitinib is potentially effective in the treatment of refractory livedoid vasculopathy - Han, Yuyang; Tu, Ping (Frontiers in Immunology, 2022)
Livedoid Vasculopathy is a chronic, recurrent, occlusive cutaneous disease characterized by the presence of erythema, purpura located on the legs, typically occurred in the ankle region or on the dorsal foot, which produce ulcerations that are intensely painful and cause a severely reduced quality of life .until now the etiopathogenesis of Livedoid vasculopathy has not been fully established.We report the successful use of Baricitinib in the treatment of refractory LV and evaluate the treatment outcomes. Livedoid vasculopathy improved with significant regression of clinical scores after baricitinib,Mean clinical score was 7.0 ± 1.6 before baricitinib and 1.4±1.2 after different weeks of baricitinib,and six out of eight patients reached a score of 0 or 2 after treatment(Figure 1).clinical findings including erythema,ulceration and pain improve in all patients(Figure 1,2). This study demonstrates the significant reduction of disease activity in LV patients who had an inadequate response to previous therapy after several weeks with baricitinib,and the patient's pain was greatly alleviated and the ulcer was relieved or disappeared.In our study the patients took baricitinib stopped other drugs gradually suggests that baricitinib could has good efficacy without additional treatment. therapy with baricitinib was well tolerated and no related severe side effects were observed in follow-up showed the safety of baricitinib.